Компактні галактики з активним зореутворенням: статистичні властивості підвибірок із пороговим значенням потоку випромінювання у лінії Hβ - Парновський, Сергій Людомирович; Ізотова, Ірина Юліанівна (Київський національний університет імені Тараса Шевченка, 2022)
З вибірки 14 тисяч локальних компактних галактик з активним зореутворенням утворено підвибірки з різними пороговими значеннями потоку випромінювання у рекомбінаційній лінії Hβ. Для підвибірок галактик досліджено функцію світності та статистичну залежність світності галактик у емісійній лінії Hβ від віку спалаху зореутворення та металічності. Отримані результати підтверджують і доповнюють висновки, зроблені під час дослідження властивостей попередніх вибірок.

We study the dependence of the luminosity of starburst galaxy on the young age (< 10 Myr) of star formation burst and metallicity. We also study the luminosity function (LF) for different subsamples of starburst galaxies. These subsamples with different threshold values of the Hβ emission line fluxes were formed from a sample of 14,000 local compact galaxies with active star formation. We obtain relations for a temporal evolution of luminosity-to-stellar mass of young stellar population ratio on the starburst age and metallicity. Luminosity functions for subsamples of galaxies with Hβ fluxes exceeding a certain threshold value are shown to differ from Schechter's LF at the high luminosity end. They are adequately described by a log-normal function with parameters determined by the maximum likelihood method. The results confirm and complement the conclusions made in previous studies of the starburst galaxy samples.
Compact galaxies with active star formation: statistical properties of subsamples with the Hβ line emission flow threshold
Keywords: галактики; зореутворення; статистичні методи; galaxies; star formation; statistical methods